SOCIAL ACTION GROUPWORK AS NEGOTIATION: CONTRADICTIONS IN THE PROCESS OF EMPOWERMENT - Keenan, Eamonn; Pinkerton, John (Groupwork)
This paper is about the process and outcomes to date of a series of discussions between a social action mother and a social work lecturer in Belfast. The central theme of the paper is contradiction within practice committed to empowerment. It is an attempt to take our discussion and theorising further by bringing it to a wider audience. Our aim is to contribute to defining the nature of social action groupwork and to identify appropriate forms of support. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.